ANALISIS PENGARUH BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Pratiwi, Intan Ratna; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2014)
This study aims to examine the effect of book-tax differences to earnings persistence on the listed manufacturing companies in Indonesia Stock Exchange during years 2010-2012. There are four independent variables, three controls variables, and one dependent variable. The independent variables are permanent differences, temporary differences, large positive book-tax differences and large negative book-tax differences. The dependent variable is earnings persistence proxied by income after changes. The control variables are components of cash flow and accrual, size, and Return on Assets (ROA). 71 manufacturing companies listed in Indonesia Stock Exchange during years 2010-2012 are used as the samples in this study. The methods of statistical analysis used multiple regresion using the program SPSS 16. The results showes that the earnings persistence will be lower if there is a large temporary differences and earnings persistence will be lower if the permanent differences is small. While, the companies with a large positive book-tax differences and large negative book-tax differences are less earnings persistence than a companies having small book-tax differences.